A comprehensive evaluation of a novel targeted-sequencing workflow for Mycobacterium species identification and anti-tuberculosis drug-resistance detection - Ou, Xichao; Pei, Shaojun; Li, Hongru; Qin, Zhonghua; Anthony, Richard; Wang, Jichun; Song, Zexuan; Xing, Ruida; Zhang, Lixia; Teng, Chong; Xia, Hui; Zhou, Yang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAlthough several World Health Organization–endorsed targeted next-generation sequencing (tNGS) assays exist for tuberculosis (TB) drug-resistance detection, their target selection and diagnostic accuracy vary widely. In this study, we developed a novel tNGS workflow (the TB Pro assay) and evaluated its performance in identifying Mycobacterium species and predicting drug resistance.MethodsThe TB Pro assay was validated for identifying 10 Mycobacterium tuberculosis complex (MTBC) and 39 nontuberculous mycobacterial (NTM) species, as well as predicting resistance to 4 first-line and 13 second-line anti-TB drugs. The limit of detection (LOD) was determined using 11 reference strains spiked in sputum. The prediction of resistance to anti-tuberculous drugs/drug classes was compared with phenotypic drug susceptibility testing (pDST) and whole-genome sequencing (WGS) using 435 clinical isolates.ResultsThe assay demonstrated high sensitivity with a calculated LOD of 3.0 CFU/ml for MTB and 1.4–16.2 CFU/ml for most NTMs, except for Mycobacterium intracellulare with 117.9 CFU/ml. Using pDST as the reference standard, the sensitivity of the TB Pro assay for the detection of resistance ranged from 74.3% (ethambutol) to 94.4% (rifampicin), with specificity values >98% for all drugs. Compared with WGS, the sensitivity of the TB Pro assay was over 98.0% for all drugs except pyrazinamide (66.7%), and the specificity values were all nearly 100.0%. Directly on sputum, the TB Pro assay showed 100% agreement with smear- and culture-positive sputum specimens.ConclusionsThe TB Pro assay represents a sensitive and specific solution for simultaneous mycobacterial identification and comprehensive drug-resistance profiling, performing robustly on both cultured isolates and direct clinical specimens.